Quality of the bottom sediment prior to dredging in the Golden Horn of Istanbul - (:unkn) unknown (MARCEL DEKKER INC, 2004)
The Golden Horn has experienced severe pollution due to uncontrolled domestic and industrial wastewater discharges until recent years. A restoration project has been developed by our universities, upon a request front Istanbul Metropolitan Municipality. Two principal alternatives for the dredging and disposal of the bottom sediments were considered: disposing on the land and disposing in the sea. Both of these alternatives include several sub-alternatives. Characterization of the sediment quality is crucially important for selecting the best alternative considering the cost, environmental impact and public acceptance. However, only a few and rather old studies were present with which it was not possible to get a comprehensive information on the critical sediment characteristics. Therefore, the aim of this study was determination of spatial distribution of sediment characteristics. The project area, at which the sediment quality determined, covers the part of the Golden Horn remaining at the upstream of Valide Sultan Bridge. The number of sampling stations were thirteen and the sediment samples were collected from 0.0 m, 5.0 m and 10.0 m from the bottom surface. The following parameters were measured on each sample: Total solids, organic matter, total phosphorus, TKN, oil and grease, total sulphur, and sediment oxygen demand (SOD). Sediment oxygen demand parameter was further divided into three fractions, namely, biological (SOD-B) and chemical (SOD-Q. Average organic content of the bottom sediment was around 10% while ammonia and sulfur exhibit very high levels. It is found that the bottom sediment is well stabilized with very low organic content below 5.0 m from the bottom surface. It can be said that, removing the upper 5 m of the bottom sediment will be enough for creating a relatively stable bottom surface which will cause oxygen depletion in the overlaying water at acceptable levels. High SOD values of the bottom sediment makes the alternatives considering disposal in the Marmara Sea and Black Sea inapplicable. High SOD-C values, especially, indicate that the sediment will cause a tremendous reduction in the oxygen concentration in a very short time at any marine environment, and even it may create anaerobic conditions. Therefore, disposal of dredged sediment into abandoned mines 4km from the Golden Horn by a pressure pipeline has been chosen as the best applicable alternative.
Keywords: dredging; Golden Horn; pollution; sediment oxygen demand; sediment quality; OXYGEN-DEMAND